Blackleg in Cattle in the Irkutsk Region - Blokhin, Andrei A.; Toropova, Nadezhda N.; Burova, Olga A.; Iashin, Ivan V.; Zakharova, Olga I. (Frontiers in Veterinary Science, 2022)
Blackleg is an acute, toxic, infectious, non-contagious disease of domestic and wild ruminants that occurs while the animals are pastured. This article describes an outbreak of blackleg on a farm in Siberia (Russia) in 2019. We provide a detailed description of the cases based on the results of comprehensive diagnostic and epidemiological investigations. For description of case and evaluation, we used the following methods: owner observations, descriptive epidemiology, clinical diagnostics, pathological examination and bacteriology. The distinctive features (in addition to the characteristic features) were as follows: the outbreak of the disease occurred in early spring when there was abundant snow cover and under unfavorable living conditions of animals and traumas; the disease appeared in both vaccinated and unvaccinated cattle; the characteristic clinical signs were low-grade fever, the absence of crepitus, and the presence of haematomas containing erythrocytes with basophilic granularity; thrombs in vessel and vacuolization in tissue of the adrenal gland. This paper aimed to present classical and new clinical and pathology changes in cattle with blackleg in winter conditions of Russian Siberia.